A COMPARATIVE EARTHWORK AND COST ANALYSIS OF IMPROVING AN EXISTING RAILWAY LINE AND CONSTRUCTING A NEW HIGH-SPEED LINE IN TURKEY - Gumus, K. A.; Gulal, V. E. (COPERNICUS GESELLSCHAFT MBH, 2016)
In the past few decades, high-speed railways have become an important transportation system due to their high operational speed, and globally, the networks of these railways have been extended. In addition, there is ongoing work on the construction of new high-speed railways as well as improving existing lines to achieve the same operational speed. To contribute to high-speed railway works in Turkey, this study compared two high-speed railway lines; an existing conventional line, the design of which was improved, and a new high-speed line. The design of an existing conventional railway line was improved according to optimal geometric characteristics of high-speed railways and an alternative line was simulated. These two lines were evaluated on three different types of land in terms of the required volume of earthworks, engineering structures and total cost. The results show that the length of the conventional line was reduced after the improvement process; however, new engineering structures are needed. Furthermore, compared to the alternative line, the track length and total length of engineering structures required for the improvement of the existing line was shorter and the volume of required earthworks was less resulting in lower costs.
Keywords: High-Speed Railways; High-Speed Track; Track Geometry; Track Design; Cost Analysis; Physical Geography; Remote Sensing; Imaging Science & Photographic Technology